Cutaneous lesions of the auricular portion of external ear - Koyuncuer, Ali (Annals of Medical Research, 2021)
Aim: Diseases coming from the external ear (outer ear canal and auricle) skin can be evaluated by many medical disciplines. External ear cutaneous lesions can be nonneoplastic, preneoplastic or neoplastic. Our aim in this study is to evaluate these surgically treated diseases.Material and Methods: All external ear tumors and tumor-like lesions that were surgically excised between 2013 and 2018 were evaluated retrospectively. The relationship between demographic features and histopathological findings and prognostic factors were analyzed.Results: Lesions were excised in the external ear in a total of 141 patients. While 91 (64.5%) of the cases were male and 50 (35.5%) were female, the average age was 33.9 (between 1 and 98 years old). While the average age of all benign tumors and non-neoplastic lesions was 27.7, 60.5% were male and 39.5% were female. The average age of malignant tumors and precursors was 67.2, the male rate was 86.4%, and the female rate was 13.6%. While cystic lesions are the most common lesion group with 27.7% (39 cases), benign non-epithelial tumors 27% (38 cases); malign epithelial tumors 15.6% (22 cases); hamartomas and similar lesions 11.3% (16 cases); inflammatory and infectious conditions 7.8% (11 cases); other formations (cutaneous deposit etc.) 7.8% (11 cases), and benign epithelial tumors 2.8% (4 cases), respectively. The most common cystic lesion was epidermal cyst and the most common benign and non-epithelial lesions were intradermal melanocytic nevi and keloid. Malignant epithelial tumors mostly detected in the external ear, squamous cell carcinoma and basal cell carcinoma. Among the hamartoma or congenital lesions and inflammatory lesions, accessory tragus and hair follicular nevus and foreign body granulomatous reaction were the most frequently observed, respectively.Among benignepithelial tumors, seborrheic keratosis was the most common.Conclusion: There are rare cutaneous lesions of the external ear that are treated with various medical and surgical specialities. In this anatomical location, tumors seen at a young age are mostly benign, while malignant tumors are more common in older ages and males, while hamartoma and similar congenital lesions are observed at a young age. A multidisciplinary approach in treatment is important both in terms of prognosis and aesthetics.
Keywords: Benign; external ear; hamartoma; malignancy